Implementation of Hygiene and Sanitation by Executive Chef in Food Processing at Kitchen Padma Resort Legian - Saputra, I Nyoman Hema; Sumerta, I Ketut Eli; Putri, Ida Ayu Karina (LPPM Universitas Dhyana Pura, 2026)
The hotel food and beverage industry demands the highest standards of hygiene and sanitation to guarantee food quality and guest safety. This study aims to analyze the implementation of hygiene and sanitation by the Executive Chef in food processing at Padma Resort Legian, identify the challenges encountered, and describe the strategies taken to overcome them. A qualitative descriptive approach was employed, with data collected through observation, interviews with the Executive Chef, and documentation at the resort kitchen from February to July 2025. The results show that Padma Resort Legian has implemented comprehensive hygiene and sanitation standards covering personal hygiene, food hygiene, kitchen area cleanliness, and equipment sanitation. The Executive Chef plays a central role in supervising Standard Operating Procedures (SOP) compliance, applying the FIFO principle, controlling supplier quality, and conducting routine staff training. Challenges include inconsistent staff discipline, cross-contamination risks from improper equipment use, limited cleaning time during peak operations, and staff turnover requiring continual re-training. Mitigation strategies include regular training programs, periodic equipment inspections, strict raw material controls, efficient waste management systems, and real-time digital monitoring of kitchen cleanliness. This study concludes that a holistic and proactive approach by the Executive Chef is essential to maintaining consistently high hygiene and sanitation standards in hotel kitchen operations.